Fundamentals of chemistry - Brescia, Frank; Arents, John; Meislich, Herbert; Turk, Amos (New York : Academic Press, 1983)
A general treatment of the major concepts and modern applications of organic, inorganic, and analytical chemistry, documented with problems to reinforce understanding of basic principles.
Chapter 1. Some fundamental tools of chemistry -- Chapter 2. Atoms, molecules, and ions -- Chapter 3. Atomic and molecular weights -- Chapter 4. Chemical formulas, equations, and nomenclature -- Chapter 5. Gases -- Chapter 6. Thermochemistry -- Chapter 7. The electronic structure of atoms -- Chapter 8. Chemical periodicity -- Chapter 9. Types of chemical bonds -- Chapter 10. Intermolecular forces and condensed states of matter -- Chapter 11. Changes of states, entropy, and free energy -- Chapter 12. Solutions -- Chapter 13. Chemical equilibrium -- Chapter 14. Acids and bases -- Chapter 15. Ionic equilibrium.
Includes index.
Keywords: CHEMISTRY